Métodos geoespaciais para caracterização morfométrica da bacia do rio Caxiuanã, Amazônia, Brasil - de Andrade, Milena Marília Nogueira; Mendes, Amílcar Carvalho (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
The aim of this article is to present a morphometric characterization of the Caxiuanã river basin (Pará, Brazil) located in the Caxiuanã National Forest, Melgaço municipality. As a conservation unit, and an isolated area with important natural resources, the use of remote sensing technologies such as radar images and Landsat can provide information about this watershed. Aspects such as drainage network characterization, basin geometry, and relief characteristics were measured through 22 morphometric parameters. This analysis was performed using geoprocessing techniques with ArcHydro and SurfaceAnalysis tools in the ArcGis program. A semi-automatic delimitation of the river basin was carried out from a fusion of radar and optical sensors. The results indicate that the drainage basin of the Caxiuanã River has a developmental dendritic pattern on the sedimentary rocks of the Alter-do-Chão geological formation and alluvial deposits. The basin has an elongated shape which indicates the concentration of the water volume at different points and a low factor form representing low tendency to floods. Morphometric parameters are used for quantitative environmental and physical characterization.
Keywords: Hydrology; Geoprocessing; Shuttle Radar Topography Mission (SRTM)